Are you alone? Measuring solitude in childhood, adolescence, and emerging adulthood - McVarnock, Alicia; Cheng, Tiffany; Polakova, Laura; Coplan, Robert J. (Frontiers in Psychiatry, 2023)
The goal of this essay was to provide an overview of how solitude has been operationally defined and measured since the year 2000 in psychological studies of children, adolescents, and emerging adults. After applying exclusionary criteria, our review of the extant literature identified N = 19 empirical studies, which we grouped into three broad methodological categories: (1) experiments/manipulations (n = 5); (2) retrospective reports (n = 7); and (3) experience sampling measures (ESM; n = 7). A review of these studies indicated considerable variation in how solitude is operationalized and measured. There is also a notable lack of studies measuring solitude in childhood. Implications for ‘what matters’ when assessing solitude are discussed, and we provide a series of suggestions for helping this research area move forward.